The extent to which a basic financial literacy programme delivered to over-indebted call-centre agents enables transformative learning to take place - Denton, Laura (School of Education, 2021)
Against the backdrop of a high level of personal over-indebtedness experienced by a large number of a Company's call-centre employees, a basic financial literacy workshop was conceptualised, implemented and offered to employees. However, while some participants found the learning helpful in alleviating their indebtedness to a lesser or greater degree, others did not. Drawing on qualitative data analysed through an interpretivist lens, this paper attempts to understand the extent to which the adult learners experienced transformative learning in the classroom. The paper's argument states that if transformative learning conditions are identified as being present in the workshop and adult learners experience a shift to a new worldview of their indebtedness situation, they will successfully implement positive changes towards alleviating their debt. The interview data for this small-group study comprised in-depth, face-to-face interviews with two participants, regarded as representative of the larger group of participants, triangulated with facilitator interview data and with workshop observation and note-taking. The thematic analysis method was used for identifying, coding and analysing the data. The themes identified related to the four main components of transformative learning theory namely, (1) triggering transformation; (2) critical reflection; (3) critical discourse and (4) willingness to act. The study showed that there were indeed components of transformative learning evident in the workshop facilitation and experienced by the study participants but that the nature of these components were embryonic. Further development of these emergent elements is required for true transformative learning to take place. Owing to the deep seated influence of a learner's worldview in prescribing how to spend his or her money, against the backdrop of the broader South African culture of indebtedness, it is only through experiencing true transformative learning that adult learners can identify and critically reflect on the belief systems that shape the way they think about and make positive changes towards their indebtedness.